Genome and Environmental Activity of a Chrysochromulina parva Virus and Its Virophages - Stough, Joshua M. A.; Yutin, Natalya; Chaban, Yuri V.; Moniruzzaman, Mohammed; Gann, Eric R.; Pound, Helena L.; Steffen, Morgan M.; Black, Jenna N.; Koonin, Eugene V.; Wilhelm, Steven W.; Short, Steven M. (Frontiers in Microbiology, 2019)
Giant viruses are ecological agents that are often involved in the top-down control of single-celled eukaryotic algae populations in aquatic ecosystems. Despite an increased interest in giant viruses since the discovery and characterization of Mimivirus and other viral giants, little is known about their physiology and ecology. In this study, we characterized the genome and functional potential of a giant virus that infects the freshwater haptophyte Chrysochromulina parva, originally isolated from Lake Ontario. This virus, CpV-BQ2, is a member of the nucleo-cytoplasmic large DNA virus (NCLDV) group and possesses a 437 kb genome encoding 503 ORFs with a GC content of 25%. Phylogenetic analyses of core NCLDV genes places CpV-BQ2 amongst the emerging group of algae-infecting Mimiviruses informally referred to as the “extended Mimiviridae”, making it the first virus of this group to be isolated from a freshwater ecosystem. During genome analyses, we also captured and described the genomes of three distinct virophages that co-occurred with CpV-BQ2 and likely exploit CpV for their own replication. These virophages belong to the polinton-like viruses (PLV) group and encompass 19 - 23 predicted genes, including all of the core PLV genes as well as several genes implicated in genome modifications. We used the CpV-BQ2 and virophage reference sequences to recruit reads from available environmental metatranscriptomic data to estimate their activity in fresh waters. We observed moderate recruitment of both virus and virophage transcripts in samples obtained during Microcystis aeruginosa blooms in Lake Erie and Lake Tai, China in 2013, with a spike in activity in one sample. Virophage transcript abundance for two of the three isolates strongly correlated with that of the CpV-BQ2. Together, the results highlight the importance of giant viruses in the environment and establish a foundation for future research on the physiology and ecology CpV-BQ2 as a model system for algal mimivirus dynamics in freshwaters.